2002
DOI: 10.1364/ao.41.001908
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-optic infrared radiometer for accurate temperature measurements

Abstract: A fiber-optic radiometer is developed for accurate noncontact temperature measurements. Of compact and novel design, it is based on replacing the usual chopper with a simple shutter. The radiometer operates in a spectral range of 5-20 microm and uses a silver-halide IR-transmitting optical fiber. The radiometer has a temperature resolution of 0.1 degrees C, a time response of 200 ms, and a spatial resolution of approximately 1 mm. Theory, simulation, radiometer design and construction, and examples of experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…We found that in general ␦ ϳ d and that in the case shown in Fig. 2 ␦ ϳ 5 m. We also found that the step height V o of the scans was linearly dependent on the temperature 18,19 T body . This made it possible to generate a calibration curve V o vs T body for the tapered fiber system, in the spectral range 8.5-13.5 m ͑i.e., subwavelength measurement͒.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…We found that in general ␦ ϳ d and that in the case shown in Fig. 2 ␦ ϳ 5 m. We also found that the step height V o of the scans was linearly dependent on the temperature 18,19 T body . This made it possible to generate a calibration curve V o vs T body for the tapered fiber system, in the spectral range 8.5-13.5 m ͑i.e., subwavelength measurement͒.…”
supporting
confidence: 62%
“…In many cases it is assumed that body ϳ 1 and A is found by performing a calibration measurement. In the past we performed single band fiber optic radiometric measurements, 18,19 which were based on these IR transmitting polycrystalline silver-halide fibers. The spatial resolution of these measurements was determined by the diameter of fiber, which was 0.9 mm.…”
mentioning
confidence: 99%
“…This method provides a very high spatial resolution as compared to the other existing contactless methods. 10,59 For example, the spatial resolution is 1 mm in fiber-optic infrared radiometer, whereas our method can go down to a few nanometers, only by probing the trapped single nanoparticle. 52,60 Probing temperature at nanoscale volume requires a fast diffusing nanoparticle, and hence, small trapping data are sufficient.…”
Section: Results and Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this technique has not been applied to AC‐coupled IR signals. Sade et al (10) relied on Δ S raw alone in characterization of their AC‐coupled PPTR system. Moreover, when using Δ S raw , the shutter speed must be constant during both the temperature calibration process and the sample temperature measurement because the time‐resolved intensity of the AC‐coupled PPTR signal depends on shutter speed.…”
Section: Resultsmentioning
confidence: 99%
“…For a Lambertian emitter, the spectral emission power is given by (10) where θ is the viewing angle relative to the normal surface. In a simulation, blackbody temperatures of 295–365 and 306–376 K were used with shutter temperatures of 295 and 306 K, respectively.…”
Section: Methodsmentioning
confidence: 99%